Crowd Monitoring: State-of-the-Art and Future Directions. Issue 6 (2nd November 2021) - Singh, Utkarsh; Determe, Jean-François; Horlin, François; De Doncker, Philippe
Abstract : With the growing concerns over public safety, the importance of crowd monitoring is being realized by various security and event management agencies worldwide. Estimation of crowd dynamics can help such agencies in the prevention of any unanticipated accidents or issues. Research on crowd monitoring has been underway since the past few decades. Conventional crowd monitoring systems mainly rely on computer vision approach. Due to predominant use of videos/ image sequences, the existing techniques may raise data privacy concerns. This has led to the development of new crowd monitoring techniques which are privacy-preserving and require minimum public participation. This paper aims to serve as a single and sufficient source of information to the concerned researchers on various aspects of crowd monitoring and also provide future directions which can be helpful in developing advanced crowd monitoring techniques.